(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Goa is one of the most popular destination for tourists. Both national and international tourists visit Goa. There were total 0.93 million people who visited Goa in 2018 and 2019 respectively (Statista, 2022). The percentage of alcohol has increased slowly and steadily. The Alcohol use has become a major problem currently in Goa. It has become a concern for individual, their family members and society at large. This paper aims to analyze how people diagnosed with alcohol lead to stress, anxiety and depression not only for self but also for their families. The impact of alcoholism in a marriage is profound. Alcohol dependence affects physical and mental health, and can cause problems with family, friends, and work. It is not only affecting the patient but also the family member, particularly maximum impact is felt on spouses. This leads to psychological impact such as depression, anxiety, suicidal ideation, stress or emotional instability. Psychiatric problem in the spouses are often given insufficient attention to the fact that the distress among the spouses is considerable. The psychological distress and morbidity among women, whose partners have alcohol problems, need to be addressed. The present study has been conducted in the state of Goa with the aim of assessing the prevalence of psychological distress in women such as stress, anxiety and depression.